Evaluation of human thermal comfort along a marathon course in Tokyo Metropolis - Kawano, K.; Oda, R.; Inagaki, A.; Nakayoshi, M. (Scientific Online Letters on the Atmosphere (SOLA), 2020)
The thermal stress along a marathon course in Tokyo is evaluated using a radiation balance model. The wet-bulb globe temperatures (WBGTs) for runners and spectators are calculated based on the surrounding building and tree geometries using the Solar Long Wave Environmental Irradiance Geometry model. Analysis is conducted in terms of summer days in August 2018, which was during the hottest summer in the past 5 years. The WBGT classification for runners along the outward leg (until around 14km) reaches the "Warning" level (WBGT=26.5°C) despite of the many shadows on the street in the early morning (until 0645 JST). The WBGT increases around the Imperial Palace because the road has a skyview factor of over 95%, and no obstacles to make shadows on the street at around 0750 JST. The WBGT classification for runners reaches the level of "Severe warning."For spectators, the difference of average WBGT from the runners are about 0.1°C although the difference could be significant locally due to partial shading on a road side.